KOMPETENSI KOMUNIKASI GURU DI MASA PANDEMIC COVID-19 - Tessa Shasrini; Dafrizal Samsudin; Eko Hero (Nusantara Hasana Berdikari, 2022)
This paper discusses how teacher communication competence during the COVID-19 Pandemic, various policies, and the implementation of health protocols were carried out to break the chain of the spread of COVID-19, which currently has an impact on teachers who are required to teach online. Communication between teachers and students in the learning process is one of the important aspects that determine the important aspects that determine the quality of the learning process. The method of implementing service activities is carried out by the seminar method with the presentation of various materials. The results of this service activity for teachers require an effective parental communication seminar so that the results achieved are more leverage. Teachers who have received training should continue to be fostered so that the program runs continuously.